Hukum Konservasi Sumber Daya Alam : Studi Konsep Desa Konservasi Berbasis Kearifan Lokal - Mohammad Choirul Anam; Asa Barno Happy Ramadhani; Bagas Sukmo Anggoro; Maya Ariska Sri Dewi; Raynaldo Adwisa Pradita; Ganesya Wahyu Aji Aryasatyani; Sigit Sapto Nugroho (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2020)
The purpose of writing this article is to find out government policies related to the management of conservation areas based on local wisdom and know the concept of conservation villages based on local wisdom. Based on the discussion results it is known that government policies in the management of conservation areas are regulated in Law Number 5 of 1990 concerning Conservation of Natural Resources Its Biodiversity and Ecosystem are aimed at achieving goals in the field of conservation. However, this Law is centralistic, where the role of government is very dominant, ignoring the rights of local / customary communities (there is no recognition and protection of access to conservation areas and the right to control and use of indigenous / local communities over Natural Resources), as well as the role of pseudo. The concept of a conservation village is an approach to a conservation model that provides opportunities for people living around conservation areas to be actively involved in efforts to manage conservation areas and at the same time as an effort to empower communities based on local wisdom. Programs in the concept of conservation villages cover the forestry and non-forestry sectors.